The Relationship Between Menstrual Length and Menstrual Cycle with Dysmenorrhea in High School Students - Dewi Novitasari Suhaid; Lorensia Panselina Widowati; Ni Nyoman Sri Artina Dewi (Universitas Andalas, 2023)
Menstruation can cause various problems including pain during menstruation or what is commonly known as dysmenorrhea. Dysmenorrhea can interfere with daily activities, including school activities for adolescents. Dysmenorrhea can occur 2-3 years after menarche. The average duration of menstruation is 3-6 days, followed by reduced blood loss from the 2nd day to the end. This causes women to feel pain on the 2nd day of their cycle due to the unmaximized detachment of the endometrium. Puberty is an important phase of life, followed by development and growth. Good knowledge will shape behavior that supports maximum growth and development. Dysmenorrhea is the number one reason why female students are absent from school. Absences lead to missing information and an impairment. The aim of this study is to determine the relationship between menstrual length and menstrual cycle with dysmenorrhea in female students. This study uses a quantitative method with a cross-sectional approach. The sample in this study consisted of 106 female students drawn by the total sampling method. Inclusion criteria were female students with menarche, and exclusion criteria were PCOS. Analysis using the Chi-Square test. The results showed that the prevalence of female students with dysmenorrhea was 71.1%. The results of the bivariate analysis test showed that there was no significant association between menstrual cycle (p value = 1.000) and menstrual length (p value = 0.852) with dysmenorrhea.